(untitled) (المجلة الدولية للبحوث العلمية, 2025)
This study examines the transformation of microlearning for creative and design practice skills in design students. This study examines the potential influence of short-form, ‘snackable’ content via platforms such as TikTok, Instagram, and YouTube. This study relies on the Cognitive Load Theory, as a theoretical framework which introduced by John Sweller, the theory suggests that working memory can only handle a limited amount of information at a time. The research design is qualitative approach, with 90 students surveyed and a corresponding analysis of the content of 15 short educational videos. The survey findings revealed a strong preference for microlearning, as 80 percent of the respondents perceived it to be effective and engaging. There are some broader implications, too: Content analysis also reveals that videos shorter than a minute that feature either voiceover or context-embedded text are the most engaging and educationally effective. The authors imply that microlearning can contribute to knowledge recall and activity engagement, innovation, and creativity, and thus serves as a supplementary or alternative method to traditional design education. Suggestions for educators and creators to take advantage of platform evolving trends in relation to learning gains are presented.